2017
DOI: 10.1101/158626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonpolio enteroviruses can also be recovered from non-reproducible cytopathology in L20B cell line

Abstract: Samples showing cytopathology (CPE) on initial inoculation into L20B cell line but with no observed or reproducible CPE on passage in L20B or RD are considered negative for both poliovirus and nonpolio enteroviruses (NPEVs). The phenomenon is termed ‘non-reproducible CPE’. Its occurrence is usually ascribed to the likely presence of reoviruses, adenoviruses and other non-enteroviruses. This study aimed to investigate the likelihood that NPEVs are also present in cases with non-reproducible CPE.Twenty-six (26) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This phenomenon of NR-CPE has been suggested to be caused by nonspecific cytotoxicity, Adenovirus or Reoviruses (to which the Rotaviruses belong) (WHO, 2007). However, we (Adeniji et al, 2018) recently showed that EVs could also contribute to NR-CPE. In this study, we go a step further to find out how often the three (Adenoviruses, group A Rotaviruses and EVs) virus types are present in cell culture supernatants (CCS) recovered from L20b cell culture tubes with NR-CPE.…”
Section: Introdutionmentioning
confidence: 94%
See 2 more Smart Citations
“…This phenomenon of NR-CPE has been suggested to be caused by nonspecific cytotoxicity, Adenovirus or Reoviruses (to which the Rotaviruses belong) (WHO, 2007). However, we (Adeniji et al, 2018) recently showed that EVs could also contribute to NR-CPE. In this study, we go a step further to find out how often the three (Adenoviruses, group A Rotaviruses and EVs) virus types are present in cell culture supernatants (CCS) recovered from L20b cell culture tubes with NR-CPE.…”
Section: Introdutionmentioning
confidence: 94%
“…to 30%(Adeniji et al, 2018) of CCSs from NR-CPE on R-L cell lines might contain EVs. D94, the EGT could not assign it to any EV type using the VP2 and VP4 data.…”
mentioning
confidence: 97%
See 1 more Smart Citation